Synthesis of 5‐hydroxymethylfurfural from glucose over carbon‐based acid–base bifunctional catalyst - Chun Wang; Qiao He; Wenhai Chen; Qunpeng Cheng; Guangsen Song; Guozhi Fan (Energy Science & Engineering, 2023)
Abstract Carbon‐based acid–base bifunctional catalyst was synthesized by the functionalization of activated carbon (AC) with 3‐mercaptopropyl trimethoxysilane, 3‐aminopropyl trimethoxysilane, and H2SO4 via sulfhydrylation, ammonifiation, and sulfonation successively. The as‐prepared catalyst of NH2‐AC‐SO3H was characterized by infrared spectroscopy, X‐ray diffraction, thermogravimetric analysis and Brunauer–Emmet–Teller specific area analysis, and it was further used for producing fuel precursor 5‐hydroxymethylfurfural (5‐HMF) from glucose. The influences of the catalyst type, ratio of acid–base groups, catalyst amount, reaction temperature, and reaction time were investigated. It was found that NH2‐AC‐SO3H revealed excellent activity, and the yield of 5‐HMF reached 71.8% under the optimized reaction conditions with a 1.3:1 mass ratio of NH2‐AC‐SO3H to glucose at 140°C for 6 h in γ‐valerolactone. The reusability of NH2‐AC‐SO3H was also performed, and only slight decreases in the conversion of glucose and the yield of 5‐HMF were observed, still giving 65.3% yield of 5‐HMF after 4 runs.